Perception of the Managerial Approach and of the High-Quality Accreditation Model Applied in Colombian Universities - Uribe Urán, Adriana P. (Cuadernos de Administración, 2014)
The article presents an analysis of the model of high-quality accreditation of university programs implemented in Colombia and of the managerial approach that characterizes universities in light of the theoretical perspectives analyzed for said purpose. The research accounts for the perceptions found in a group of players related directly with the administrative process of Colombian universities. The qualitative methodology was employed because it permits flexible analysis and interpretation of the study topic; the phenomenological and hermeneutic methods were used because of their validity in accomplishing objectivity and understanding of the phenomenon investigated. As information collection technique, the semistructured interview was used with academic directors. The results found are not generalizable; they merely measure the perceptions of a group of players and can be a guiding parameter of a reality. The perception found with respect to the managerial approach applied in Colombian universities indicates that these are being managed under approaches traditionally used in production-type enterprises and are based on the application of the administrative process to accomplish efficiency and effectiveness. With respect to the current high-quality accreditation model implemented in universities, it is found that it should be contextualized according to the specific conditions of the universities subjected to the process, given that although it permits improving the educational process, as well as the conditions to offer the service, it is not very equitable and its results are not sustained over time.